Of Mice and Men Play Still - unknown:::Creator::::::::::::
George (Wallace Ford), Lennie (Broderick Crawford) and Curley's wife (Clare Luce) in John Steinbeck's 'Of Mice and Men,' on the 'Bunkroom Stage' of an unidentified theater in New York.